Diabetes in the Cape Town Metropole – a secondary analysis of the diabetes cascade database 2015 - 2020 - Boake, Megan Wilson (Stellenbosch : Stellenbosch University, 2021)
Thesis (MFamMed)--Stellenbosch University, 2021.